2017
DOI: 10.3920/bm2016.0102
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus thermophilus fermented milk reduces serum MDA-LDL and blood pressure in healthy and mildly hypercholesterolaemic adults

Abstract: Low-density lipoprotein (LDL)-cholesterol, malondialdehyde-modified low-density lipoprotein (MDA-LDL), MDA-LDL/LDL-cholesterol in serum, and blood pressure are considered useful risk markers of cardiovascular diseases. This study aimed to examine whether a fermented milk containing Streptococcus thermophilus YIT 2001 (ST), which has high anti-oxidative activity, would benefit healthy and mildly hyper-LDL-cholesterolaemic adults via a randomised, double-blind, placebo-controlled trial. ST-fermented milk or non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The mean probiotic administration was 67.01 ± 38.72 days (range = 28–186 days). Probiotic, not synbiotic, interventions were predominantly conducted ( n = 54) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 88 , 89 ]. Probiotic powders were administered in 15 studies [ 31 , 36 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The mean probiotic administration was 67.01 ± 38.72 days (range = 28–186 days). Probiotic, not synbiotic, interventions were predominantly conducted ( n = 54) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 88 , 89 ]. Probiotic powders were administered in 15 studies [ 31 , 36 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The results from subgroup analysis showed that SBP had a significant decreasement in pre-HTN and HTN subset (WMD: −5.14 mmHg; 95% CI: −8.45, −1.83, P < .001); as outlined in Table 2. Overall, 24 eligible studies [15][16][17][19][20][21][22][23][24][25][26]28,29,[32][33][34][35][36][37][38][39][40][41][42] (with 31 treatment arms), including a total of 2102 participants, examined the effect of PFM supplementation on DBP. Combining the findings based on random-effects model, we found that DBP had not any significant change after PFM supplementation (WMD: −1.04 mmHg, 95% CI: −2.51 to 0.44, P = .167) compared to the control group with significant heterogeneity between-study (I 2 = 79.2%, P < .001) (Figure 3), subgroup analysis could not explain this heterogeneity.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…[48] Numerous of the earlier clinical trials noted that increased intake of fermented dairy products reduces the risk of high BP. [21,22,34,36,37,41] However, there is no general agreement on this point. [25,33,35] Our findings were in contrast with earlier meta-analyses that evaluated the effect of PFM on BP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations